Determinants of COVID-19 Vaccine Engagement in Algeria: A Population-Based Study With Systematic Review of Studies From Arab Countries of the MENA Region - Kacimi, Salah Eddine Oussama; Klouche-Djedid, Selma Nihel; Riffi, Omar; Belaouni, Hadj Ahmed; Yasmin, Farah; Essar, Mohammad Yasir; Taouza, Fatma Asma; Belakhdar, Yasmine; Fellah, Saliha Chiboub; Benmelouka, Amira Yasmine; Ahmed, Shoaib; Aloulou, Mohammad; et al. (Frontiers in Public Health, 2022)
Background The Algerian COVID-19 vaccination campaign, which started at the end of January 2021, is marked by a slowly ascending curve despite the deployed resources. To tackle the issue, we assessed the levels and explored determinants of engagement toward the COVID-19 vaccine among the Algerian population. Methods A nationwide, online-based cross-sectional study was conducted between March 27 and April 30, 2021. A two-stage stratified snowball sampling method was used to include an equivalent number of participants from the four cardinal regions of the country. A vaccine engagement scale was developed, defining vaccine engagement as a multidimensional parameter (5 items) that combined self-stated acceptance and willingness with perceived safety and efficacy of the vaccine. An Engagement score was calculated and the median was used to define engagement vs. non-engagement. Sociodemographic and clinical data, perceptions about COVID-19, and levels of adherence to preventive measures were analyzed as predictors for non-engagement. Results We included 1,019 participants, 54% were female and 64% were aged 18–29 years. Overall, there were low rates of self-declared acceptance (26%) and willingness (21%) to take the vaccine, as well as low levels of agreement regarding vaccine safety (21%) and efficacy (30%). Thus, the vaccine engagement rate was estimated at 33.5%, and ranged between 29.6-38.5% depending on the region (p > 0.05). Non-engagement was independently associated with female gender (OR = 2.31, p < 0.001), low adherence level to preventive measures (OR = 6.93, p < 0.001), private-sector jobs (OR = 0.53, p = 0.038), perceived COVID-19 severity (OR = 0.66, p = 0.014), and fear from contracting the disease (OR = 0.56, p = 0.018). Concern about vaccine side effects (72.0%) and exigence for more efficacy and safety studies (48.3%) were the most commonly reported barrier and enabler for vaccine acceptance respectively; whereas beliefs in the conspiracy theory were reported by 23.4%. Conclusions The very low rates of vaccine engagement among the Algerian population probably explain the slow ascension of the vaccination curve in the country. Vaccine awareness campaigns should be implemented to address the multiple misconceptions and enhance the levels of knowledge and perception both about the disease and the vaccine, by prioritizing target populations and engaging both healthcare workers and the general population.